Contributions to Lateral Balance Control in Ambulatory Older Adults - Sparto, PJ (Aging Clin Exp Res, 2017)
BACKGROUND: In older adults, impaired control of standing balance in the lateral direction is associated with increased risk of falling. Assessing the factors that contribute to impaired standing balance control may identify areas to address to reduce falls risk. AIM: To investigate the contributions of physiological factors to standing lateral balance control. METHODS: Two hundred twenty-two participants from the Pittsburgh site of the Health, Aging and Body Composition Study had lateral balance control assessed using a clinical sensory integration balance test (standing on level and foam surface with eyes open and closed) and a lateral center of pressure tracking test using visual feedback. The center of pressure was recorded from a force platform. Multiple linear regression models examined contributors of lateral control of balance performance, including concurrently measured tests of lower extremity sensation, knee extensor strength, executive function, and clinical balance tests. Models were adjusted for age, body mass index, and sex. RESULTS: Larger lateral sway during the sensory integration test performed on foam was associated with longer repeated chair stands time. During the lateral center of pressure tracking task, the error in tracking increased at higher frequencies; greater error was associated with worse executive function. The relationship between sway performance and physical and cognitive function differed between women and men. DISCUSSION: Contributors to control of lateral balance were task-dependent. Lateral standing performance on an unstable surface may be more dependent upon general lower extremity strength, whereas visual tracking performance may be more dependent upon cognitive factors. CONCLUSIONS: Lateral balance control in ambulatory older adults is associated with deficits in strength and executive function.